Dilema Penerapan Denda Damai Oleh Jaksa Dalam Tindak Pidana Korupsi: Upaya Mewujudkan Pemulihan Ekonomi Nasional - Handrawan (Jurnal Litigasi)
The Prosecutor's Office Law authorizes prosecutors to use peace fines in economic crimes, but on the other hand, the Corruption Eradication Law explicitly states that the return of state losses does not eliminate the punishment for corruption perpetrators. This conflict of norms has led to debates about the legality and effectiveness of peaceful fines in corruption cases. This study aims to analyze the conflict of norms in the application of peaceful fines and explore its application in the principle of systematic lex specialis. From this study, it is found that there is a lack of clarity in the regulations regarding whether corruption can be categorized as an economic crime that can be resolved with an amicable fine.The application of amicable fines in corruption crimes can provide benefits in the recovery of state finances, but also has the potential to weaken theprinciple of legal certainty and deterrent effects for perpetrators. Therefore, it is necessary to harmonize the regulations between the Prosecutor's Office Law and the Corruption Eradication Law to avoid overlapping rules.